2013
DOI: 10.4103/2141-9248.117960
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk behavior in persons with severe mental disorders in a psychiatric hospital in Ogun, Nigeria

Abstract: Background:Few studies in Nigeria have investigated HIV risk behavior among persons with severe mental disorders. This study examined HIV risk behavior and associated factors among patients receiving treatment at a Nigerian psychiatric hospital.Aim:To determine the HIV risk behavior in persons with severe mental disorders in a psychiatric hospital.Subjects and Methods:This was a cross-sectional survey involving 102 persons with serious mental disorders receiving treatment at a major psychiatric facility in Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Mental health problems can increase risk of HIV acquisition through both direct and indirect pathways. Although people with SMI tend to be less sexually active compared with the general population, sexually active adolescents and adults with SMI evidence higher risk sexual behavior, including inconsistent condom use, having multiple sexual partners, trading sex, and drinking alcohol before sex [2329]. The risk of HIV infection may also increase with severity of psychiatric illness.…”
Section: Mental Health and Hiv Acquisitionmentioning
confidence: 99%
“…Mental health problems can increase risk of HIV acquisition through both direct and indirect pathways. Although people with SMI tend to be less sexually active compared with the general population, sexually active adolescents and adults with SMI evidence higher risk sexual behavior, including inconsistent condom use, having multiple sexual partners, trading sex, and drinking alcohol before sex [2329]. The risk of HIV infection may also increase with severity of psychiatric illness.…”
Section: Mental Health and Hiv Acquisitionmentioning
confidence: 99%
“…In the UK condom use was very inconsistent (around 8%), drug or alcohol use during sexual intercourse was common, and sexual exchange (for money, drugs or other goods), around 12% of those who were active had sex with a partner who was a known drug user [2]. In Nigeria 38.2% reported two or more sexual partners, 5.9% reported sex trading and 80.8% inconsistent use of condom [8], community-based cross-sectional study conducted in New York 62% had multiple sexual partners, 50% took part in sex exchange, 45% of the active patients used drugs or alcohol during sex, which may affect risk-taking behavior [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional study conducted on Italy stated that 83% of schizophrenia engage in high-risk sexual activity at which (58% had multiple sexual partners, 25% of them had almost never used a condom) [9]. A case–control study conducted on Turkey of risky sexual behaviors of among diagnosis of schizophrenia was 26%, such as sex with multiple sexual partners 6%, sexual intercourse with different partners 10%, sexual activity under influence of alcohol or other drugs 10% in participants [10] in India, 59% of had a history of risky sexual behavior [11], Nigeria (48%), of the prevalence of risky sexual behavior [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a survey of 102 patients from a Nigerian psychiatric hospital, the majority of those who reported a lifetime history of sexual activity also reported engagement in HIV risk behaviors, which included inconsistent condom use, having multiple partners, and sex trading [7]. Additionally, these researchers found that alcohol use was associated with HIV risk behavior, while demographic factors were not.…”
Section: Primary Hiv Preventionmentioning
confidence: 99%
“…Although there is some research to suggest that HIV risk behavior is the direct result of psychiatric symptoms (e.g., hypersexuality during manic episodes) [5, 6], growing evidence suggests that HIV transmission risk in SMI populations is much more complex and often occurs as an indirect consequence of multiple individual, social, and system factors [711]. Factors such as a history of homelessness, experience of sexual violence, early sexual debut, drug or alcohol use during sex, and lifetime illicit drug use, which are disproportionately common among persons with SMI, increase risk of HIV infection.…”
Section: Introductionmentioning
confidence: 99%